2016
DOI: 10.1111/cas.12980
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities to various epidermal growth factor receptor‐tyrosine kinase inhibitors of uncommon epidermal growth factor receptor mutations L861Q and S768I: What is the optimal epidermal growth factor receptor‐tyrosine kinase inhibitor?

Abstract: Most patients with non‐small cell lung cancer (NSCLC) harboring common epidermal growth factor receptor (EGFR) mutations, such as deletions in exon 19 or the L858R mutation in exon 21, respond dramatically to EGFR tyrosine kinase inhibitors (EGFR‐TKI), and their sensitivities to various EGFR‐TKI have been well characterized. Our previous article showed the in vitro sensitivities of EGFR exon 18 mutations to EGFR‐TKI, but little information regarding the sensitivities of other uncommon EGFR mutations is availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 43 publications
3
58
0
1
Order By: Relevance
“…Previous clinical reports have found that patients with NSCLC harboring uncommon mutations of EGFR tend to be less sensitive to reversible (first‐generation) EGFR‐TKI compared with those positive for common EGFR mutations . However, subset analysis of the LUX‐Lung 3 and LUX‐Lung 6 trials showed that the objective response rate for the second‐generation EGFR‐TKI afatinib was 77.8% and 56.3% in patients with G719X or L861Q mutations of EGFR , respectively .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous clinical reports have found that patients with NSCLC harboring uncommon mutations of EGFR tend to be less sensitive to reversible (first‐generation) EGFR‐TKI compared with those positive for common EGFR mutations . However, subset analysis of the LUX‐Lung 3 and LUX‐Lung 6 trials showed that the objective response rate for the second‐generation EGFR‐TKI afatinib was 77.8% and 56.3% in patients with G719X or L861Q mutations of EGFR , respectively .…”
Section: Discussionmentioning
confidence: 96%
“…However, subset analysis of the LUX‐Lung 3 and LUX‐Lung 6 trials showed that the objective response rate for the second‐generation EGFR‐TKI afatinib was 77.8% and 56.3% in patients with G719X or L861Q mutations of EGFR , respectively . In vitro studies found that EGFR with a single G719X mutation was more sensitive to second‐generation than to first‐generation or third‐generation EGFR‐TKI, and that EGFR with a single L861Q mutation was sensitive to both second‐generation and third‐generation EGFR‐TKI . These data thus suggest that afatinib is the most appropriate EGFR‐TKI for NSCLC harboring uncommon mutations of EGFR .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance mutation T790M in exon 20 was found in two cases, one de novo mutation and the other one being probably selected under treatment pressure, since this patient was previously treated with TKIs. Other uncommon described mutations found in our series (p.L861Q and p.768I) have been suggested as less sensitive for first-generation TKIs [46], but in vitro experimental research suggests sensitivity for second- and third-generation TKIs [47]. Lastly, some very rare mutations in exon 21 were observed: p.P848L ( n = 2), reported as a resistant to TKIs germ-line mutation by Prim et al [48], and p.A840T ( n = 1), also showing no benefit from TKIs [49].…”
Section: Discussionmentioning
confidence: 99%
“…In this in vitro study, afatinib showed very low half maximal inhibitory concentration (IC 50 ) value to S768I mutation, but both gefitinib and erlotinib had high values of IC 50. Osimertinib was less sensitive to S768I mutation than afatinib [6, 11]. A Korean phase II trial showed that osimertinib achieved partial response in 3 patients of 8 with EGFR-TKI naïve S768I mutation (ORR, 37.5%) [12].…”
Section: Discussionmentioning
confidence: 99%